Modulation Found in Translation of Poco Lo Coco Movie - Widya Ningrum; Diana Chitra Hasan; Al Azwad Fauzan (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2018)
The aims of this study are to find the types of modulation strategy in translation Poco Lo Coco movie and describe the accuracy of modulation of English to Indonesian. The research used a descriptive qualitative method. The data of this  research are the utterances or sentences in movie subtitle both English and Indonesian with the source of the data of this research is Poco Lo coco movie.The data collected by watching the movie, and categorized the collected data based on types of modulation strategy and asses accuracy of modulation. The writer find out there are three types of modulation found in the Poco Lo Coco movie such as free modulation, addiction or creation, point of view shift.While the translation using modulation procedure could be concluded categorized as accurate, less accurate and inaccurate.Based on the findings, it can be concluded that there are three from eleven types of modulation are found in the movie subtitle:Poco Lo coco.